Clinical assessment and radiograph following blunt chest trauma. Issue 2 (June 1989) - Dunlop, M G; Beattie, T F; Preston, P G; Steedman, D J
Abstract : This study was undertaken to assess the accuracy of clinical examination in predicting significant injury following blunt chest trauma and to determine whether more selective use of frontal chest radiography could be achieved.